Targeting fibroblast activation protein in cancer - Prospects and caveats - Busek, Petr; Mateu, Rosana; Zubaľ, Michal; Kotackova, Lenka; Sedo, Aleksi (Frontiers in bioscience (Landmark edition), 2018)
Fibroblast activation protein (FAP, seprase) is a serine protease with post-proline dipeptidyl peptidase and endopeptidase enzymatic activity. FAP is upregulated in several tumor types, while its expression in healthy adult tissues is scarce. FAP molecule itself and FAP+ stromal cells play an important although probably context-dependent and tumor type-specific pathogenetic role in tumor progression. We provide an overview of FAP expression under both physiological and pathological conditions with focus on human malignancies. We also review and critically analyze the results of studies which used various strategies for the therapeutic targeting of FAP including the use of low molecular weight inhibitors, FAP activated prodrugs, anti-FAP antibodies and their conjugates, FAP-CAR T cells, and FAP vaccines. A unique enzymatic activity and selective expression in tumor microenvironment make FAP a promising therapeutic target. A better understanding of its role in individual tumor types, careful selection of patients, and identification of suitable combinations with currently available anticancer treatments will be critical for a successful translation of preclinically tested approaches of FAP targeting into clinical setting.
Keywords: Membrane Proteins; regulace genové exprese u nádorů; Humans; Serine Endopeptidases; regulace genové exprese enzymů; Molecular Targeted Therapy; lidé; želatinasy; serinové endopeptidasy; Neoplasms; cílená molekulární terapie; Tumor Microenvironment; nádory; inhibitory enzymů; nádorové mikroprostředí; membránové proteiny; Gene Expression Regulation, Enzymologic; Gelatinases; Gene Expression Regulation, Neoplastic; Enzyme Inhibitors